Railway geotechnics - Li, Dingqing; Hyslip, James P.; Sussmann, Theodore R.; Chrismer, S. M. (CRC Press/Taylor & Francis, 2016)
Railway Geotechnics is written primarily for professionals and graduate students, and begins with the fundamentals and basic principles, leading in to practical applications. The authors bring considerable experience and expertise, with many years of research and development, academia, railway operations, and consulting.